Safety Nets and Safety Ropes : Who Benefited from Two Indonesian Crisis Programs—The "Poor" or the "Shocked"? - Sumarto, Sudarno; Suryahadi, Asep; Pritchett, Lant (World Bank, Washington, DC, 2015)
Imagine several mountain climbers, scaling a cliff face, who want protection from falling. One way to protect them would be to place a net at the bottom of the cliff to catch any climber just before he hits the ground. Another would be to provide a rope, and a set of movable devices that can be attached to the cliff; as the climbers scale the cliff, they attach the rope at higher levels, so that if a climber falls, he falls only by the length of the rope. In this paper, the :safety net" guarantees against a fall past an absolute level; the "safety rope" guarantees against a fall of more than a given distance. The safety net is concerned with an increase in poverty; the safety rope mitigates risk through social insurance, or social protection. Calculations of the benefit incidence, and targeting effectiveness of safety net programs, typically examine only the relationship between a household's current expenditures, and program participation. But in programs that respond to an economic shock, or intend to mitigate household risk, it is not only the current level of expenditures that matters, but also changes in expenditures. Safety net programs may intend to benefit only the currently poor; programs to mitigate shocks ("safety rope" programs) may intend to provide transfers to those whose incomes have fallen, even if they have not fallen below an absolute poverty threshold. The authors examine the targeting performance of tow programs, created to respond to the social impacts of Indonesia's crisis. They find strong evidence that one program, subsidized sales of rice targeted to the permanently poor, was only weakly related to the shock in consumption spending. A job creation program was much more responsive to changes in spending. A Household that started in the third quintile in expenditures in 1997, and fell to the lowest quintile between 1997, and 1998, was four times as likely to have participated in the job creation program as a household starting in the third quintile in 1997, but experiencing a positive shock. But the household experiencing a negative shock, was only fifty percent more likely to have received subsidized rice, than a household experiencing a positive shock.